Pengembangan Usaha Peternakan Terpadu untuk Peningkatan Ketahanan Pangan dan Gizi Keluarga Peternak Kecil di Kelurahan Mokoau - Badaruddin, Rusli; Saili, Takdir; Asminaya, Nur Santy; Bahtiar, Bahtiar; Putri, Anindyaningrum Zainal; Agustina, Dian; Sandiah, Natsir (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance food security and family nutrition among small-scale livestock farmers through the implementation of an integrated livestock farming system in Mokoau Village, Kambu District, Kendari City. Most residents in this area rely on small-scale livestock farming with traditional management practices, resulting in suboptimal livestock productivity and inadequate family nutrition. The program provided training, technical assistance, and implementation of an integrated system combining livestock and crop farming to optimize local resource utilization. The method applied a participatory approach, consisting of several stages: initial survey, training, technical mentoring, and evaluation. Data were collected through observation, questionnaires, and interviews with farmers. The results showed significant improvement in livestock productivity, with an average increase in livestock body weight by 12–15% and egg production by 20%. Family protein consumption also increased by approximately 30% per week, indicating a tangible improvement in family nutrition quality. Furthermore, farmers’ knowledge and skills in feed management, livestock health, and waste utilization improved considerably. Livestock waste was processed into organic fertilizer for food crops, supporting the sustainability of the integrated livestock system. Overall, the program proved effective in enhancing productivity, food security, and the welfare of smallholder livestock farmers in Mokoau Village, and it serves as a sustainable community empowerment model for rural development.